Do ethnic minorities 'stretch' their time? Evidence from the UK time use survey - Anzelika Zaiceva; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper investigates the effect of ethnicity on time spent on overlapped household production, work and leisure activities employing the 2000-2001 UK Time Use Survey. We find that, unconditionally, white females manage to stretch their time the most by an additional 233 minutes per day and non-white men stretch their time the least. The three secondary activities that are most often combined with other (primary) activities in terms of time spent on them are social activities including resting, passive leisure and childcare. Regression results indicate that non-white ethnic minorities engage less in multitasking than whites, with Pakistani and Bangladeshi males spending the least time. The gap is present for both ethnic minority males and females, although females in general engage more in multitasking. The effect is also heterogeneous across different sub-groups. We then discuss several potential interpretations and investigate whether these differences in behavior may also relate to opportunity costs of non-market time, different preferences and tastes of ethnic minorities, integration experience, family composition, household productivity and other.
Keywords: J22; J15; 330; Time use; multitasking; ethnic minorities; UK; Zeitallokation; Haushaltsproduktion; Erwerbstätigkeit; Ethnische Gruppe; Geschlecht; Großbritannien